Evaluation of Education and Training Programs for Civil Servants’ Managerial Competence Using the Kirkpatrick Model - Dhani Sudirman; Farihin Nur; Iman Subasman; Hendar Hendar; Asep Supriatna (Journal of Educational Studies, 2026)
This study aims to examines the evaluation of education and training programs aimed at enhancing civil servants’ managerial competence using the Kirkpatrick Model. A qualitative approach was employed, using in-depth interviews, observation, and documentation as data collection techniques. The data were analyzed through thematic analysis to identify key patterns and findings. The results indicate that the training program achieved positive outcomes at the reaction and learning levels, where participants demonstrated increased knowledge, analytical skills, and improved perceptions of the training. However, the effectiveness decreased at the behavior and results levels, as the application of learning in the workplace was not consistent and organizational impacts were not systematically measured. These findings suggest that while training programs are effective in improving individual competencies, their long-term success depends on organizational support and structured evaluation systems. Strengthening post-training strategies and evaluation mechanisms is essential to ensure sustainable impacts of training programs in the public sector.